PENGARUH PENGANGGARAN PARTISIPATIF DAN TEKANAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI (Studi Pada Satuan Kerja Perangkat Daerah Kota Palu) - Ardin, Ardin (Katalogis, 2017)
The aim of this study is to determine and analyze the effect of partial independent variables are a participatory budgeting and a budgetary emphasis to the dependent variable budgetary slack with locus of control as a moderating variable throughout SKPD city of Palu. This research is a quantitative research using a census sampling method by distributing questionnaires to entire SKPD city of Palu. Simple regression analysis and residual test, which supported by SPSS version 21,00 are used. The result of this research suggests that participatory budgeting has a negative significant effect towards the budgetary slack, while budget emphasis has a positive significant effect. Locus of control is not moderating variables that influence the effect of participatory budgeting and budget emphasis to budgetary slack in SKPD city ofÂ Palu.